Power Over Sexuality in Joss Wibisono’s Rijsttafel Versus Entrecôte - Giovani, Evelin (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
This research is aimed to describe the power of sexuality in Joss Wibisono's Rijsttafel Versus Entrecôte short story using Foucault's concept of power juridic-discursive which investigates the negative relation rulers toward homosexual and assertively power some rules by creating a cycle of prohibition, censorship, and uniformity of the apparatus. This research was conducted by using qualitative research techniques that analyzed the short story Rijsttafel Versus Entrecôte by Joss Wibisono through a post-structural approach. Data is obtained through hermeneutic reading. Based on the conducted research, it can be concluded that in this short story the power over sexuality was regulated by the Dutch colonial government through the implantation of inferior idea on the values and culture of Bumiputra; the sexuality policymaking that applies to the people of Bumiputra; the creation of discomfort, anxiety, and fear of discuss about homosexuality; and the uniformity of Dutch colonial values over its colonies. The relation between text and actualization in society is the force of power over sexuality that has been going on for a long time and also influenced by the Dutch colonial government’s point of view over homosexual.